Charged particle multiplicity in e(+)e(-)-> q(q)over-bar events at 161 and 172 GeV and from the decay of the W boson - Abreu, P; Adam, W; Adye, T; Ajinenko, I; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andersson, P; Andreazza, A; et al. (1998)
The data collected by DELPHI in 1996 have been used to measure the average charged particle multiplicities and dispersions in qq̄ events at centre-of-mass energies of √s = 161 GeV and √s = 172 GeV, and the average charge multiplicity in WW events at √s = 172 GeV. The multiplicities in qq̄ events are consistent with the evolution predicted by QCD. The dispersions in the multiplicity distributions are consistent with Koba-Nielsen-Olesen (KNO) scaling. The average multiplicity of charged particles in hadronic W decays has been measured for the first time; its value, 19.23 ± 0.74(stat + syst), is consistent with that expected for an e+e- interaction at a centre-of-mass energy equal to the W mass. The charged particle multiplicity in W decays shows no evidence of effects of colour reconnection between partons from different W's at the present level of statistics. © 1998 Elsevier Science B.V.